Grammar practice activities : A practical guide for teachers - Ur, Penny (Cambridge : Cambridge University Press, 1988)
For the teacher who wishes to combine grammar teaching with a broadly communicative methodology, this book is an invaluable resource.
Keywords: English language; English grammar; English language -- Grammar; English language -- Study and teaching -- Foreign speakers